2019
DOI: 10.20452/pamw.14985
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema affects the number and appearance of solitary pulmonary nodules identified in chest low-dose computed tomography: a study on high risk lung cancer screenees recruited in Silesian District

Abstract: INTROduCTION Chest low-dose computed tomography (LDCT) has recently been proved effective in lung cancer screening. ObjECTIvEs We aimed to assess the association between the occurrence of emphysema and solitary pulmonary nodules (SPNs) in first-round screening with LDCT. PATIENTs ANd mEThOds A total of 601 asymptomatic volunteers with a smoking history underwent LDCT; 523 patients were assigned to one of the following groups: E, emphysema without nodules (n = 103); E + N, emphysema with coexisting nodules (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…When we focused on the participants with lung nodules, the presence of emphysema was related to larger nodules and participants with 2–3 nodules. This is consistent with findings of a study by Ewa et al, who found that emphysema is more frequently associated with larger and multiple lung nodules [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When we focused on the participants with lung nodules, the presence of emphysema was related to larger nodules and participants with 2–3 nodules. This is consistent with findings of a study by Ewa et al, who found that emphysema is more frequently associated with larger and multiple lung nodules [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, PM 2.5 could also induce changes in long-noncoding RNAs through reactive oxygen species, thereby promoting autophagy and proliferation of lung cells, further leading to the occurrence of emphysema and lung nodules [ 39 ]. Finally, the main pathological feature of emphysema is the permanent enlargement of airspaces distal to the terminal bronchioles, which will be the risk factor for neoplastic transformation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of such a case is shown in Figure 4 . Similarly, omitting the presence of other diseases like emphysema could also influence the number and characteristics of nodules [ 34 ] and so, the performance of that algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…Screening programs using low-dose CT improve early detection of lung cancer in high-risk populations. Pulmonary nodules, also multiple, may be detected in a significant proportion of screenees [41]. Radiomics is a modality that may also enhance the effectiveness of lung cancer screening programs [42].…”
Section: Discussionmentioning
confidence: 99%